Upaya Peningkatan Pengetahuan Remaja tentang Pencegahan HIV/AIDS dengan Audio Visual - Naqzi, Niam Three; Ulfah, Mariah; Maryoto, Madyo (Yayasan Inspirasi El Burhani, 2025)
Introduction: HIV/AIDS remains a global health issue with increasing incidence rates, including in Indonesia. Adolescents are a vulnerable group due to limited information and the absence of a specific curriculum on reproductive health in schools. Prevention efforts can be carried out through socialization and health education, one of which is the use of audio-visual media that is more interesting and easier to understand. Objective: This activity aims to measure adolescents’ knowledge before and after HIV/AIDS prevention education using audio-visual media. Method: The activity was conducted at SMK Al Hikmah 1 Benda Sirampog on May 22, 2025, involving 20 male participants. The implementation included a pre-survey and media preparation, a pre-test, HIV/AIDS education through lectures, discussions, and question-and-answer sessions, followed by a post-test to assess the increase in knowledge. Result: The results showed a significant increase in adolescents’ knowledge after audio-visual education, from 13 respondents (65%) in the poor category and 7 respondents (35%) in the fair category, to 19 respondents (95%) in the good category and only 1 respondent (5%) in the fair category. The average knowledge score also increased from 1.35 to 2.95, confirming the effectiveness of audio-visual media in improving understanding of HIV/AIDS. Conclusion: Audiovisual-based health education has been proven effective in increasing adolescents' knowledge about HIV/AIDS, making it a viable intervention strategy. These findings confirm that interactive educational media can be a powerful alternative in building awareness and encouraging HIV/AIDS prevention among adolescents.